2020
DOI: 10.3390/su12072659
|View full text |Cite
|
Sign up to set email alerts
|

No polarization–Expected Values of Climate Change Impacts among European Forest Professionals and Scientists

Abstract: The role of values in climate-related decision-making is a prominent theme of climate communication research. The present study examines whether forest professionals are more driven by values than scientists are, and if this results in value polarization. A questionnaire was designed to elicit and assess the values assigned to expected effects of climate change by forest professionals and scientists working on forests and climate change in Europe. The countries involved covered a north-to-south and west-to-eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…Since many, if not most, of the climate change impacts that are expected to emerge, will do so in future decades and even centuries, these findings are important. It should be noted that in line with [18], the present study was only concerned with intentional adaptation and mitigation and that there might be unintentional causal interaction between adaptation and mitigation behaviours which the respondents did not take into account (but which, for instance, societal institutions are well aware of [8]). With this qualification in mind, was it to be expected that citizens of Malmö would favour decision-making promoting global (rather than local) and temporally distant (rather than more immediate) benefits?…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Since many, if not most, of the climate change impacts that are expected to emerge, will do so in future decades and even centuries, these findings are important. It should be noted that in line with [18], the present study was only concerned with intentional adaptation and mitigation and that there might be unintentional causal interaction between adaptation and mitigation behaviours which the respondents did not take into account (but which, for instance, societal institutions are well aware of [8]). With this qualification in mind, was it to be expected that citizens of Malmö would favour decision-making promoting global (rather than local) and temporally distant (rather than more immediate) benefits?…”
Section: Discussionmentioning
confidence: 98%
“…The fraction of mitigation or adaptation decisions observed was used as the rule for determining if the probability estimate is great enough to be classified into the positive category (see [3]). The variable net value of expected impacts (homogeneity of expected climate change values in [18]) was used in both of the univariate models…”
Section: Statistical Analysis and Machine Learning Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Public understanding of the scale and scope of climate change as well as the resulting environmental consequences is key to reducing consumption, changing behavior, and developing appropriate environmental attitudes [35][36][37][38]. It is also an important element to improve communication [36], whose task is to engage in dialogue with societies and decision-makers in order to implement real actions to curb climate change. According to Willamson et al [37], social factors influence individual assessment of perceptions of environmental issues, which was also confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The forest service decision-makers may have different perceptions on climate change adaptation around the globe. Persson et al (2020) studied whether forest experts are more values-led than scientists regarding speci c climate change effects on forests in their countries and whether this leads to value polarization. They found that European forest experts and scientists do not have divided values but few gaps between them.…”
Section: Introductionmentioning
confidence: 99%